White Matter Hyperintensities of the Corpus Callosum Are Associated With Clinical Severity in CADASIL. Issue 4 (23rd February 2023) - Ouin, Elisa; Dimitrovic, Ana; Grosset, Lina; Lebenberg, Jessica; Guillonnet, Antoine; Guichard, Jean-Pierre; Hervé, Dominique; Chabriat, Hugues; Jouvent, Eric
Abstract : Background: In CADASIL (Cerebral Autosomal Dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy), clinical severity is not related to the total burden of white matter hyperintensities (WMHs), presumably because of heterogeneous underlying tissue alterations. We aimed to investigate whether WMHs in the corpus callosum (WMHCC ) are due to secondary degeneration and related to clinical severity. Methods: We evaluated data from 228 CADASIL patients included in an ongoing prospective cohort with available 3-dimensional fluid-attenuated inversion recovery magnetic resonance imaging sequences. We analyzed in a blind manner WMHCC and lacunes in presumably connected areas to determine whether WMHCC are related to secondary degeneration. We evaluated the links between WMHCC and the Mattis dementia rating scale and the modified Rankin Scale—widely used measures of global cognitive performances and disability, respectively. Linear regression models were adjusted for age, sex, level of education, brain volume, number of lacunes, and volume of WMH. Results: Among 228 patients, only 105 (46%) had WMHCC while all had WMH in the rest of the white matter. In 74% of cases, WMHCC crossed a presumably connected nearby lacune, which was significantly higher than the expected value if the spatial distributions of WMHCC and nearby lacunes were unrelated (11%; P <0.001). Patients with WMHCC had worse Mattis dementia rating scale (median [P25–P75], 138 [122–142] versus 143 [140–143]; P <0.001) and worse modified Rankin Scale (2 [1–3] versus 1 [0–1]; P <0.001). In adjusted models, Mattis dementia rating scale was significantly associated with WMHCC (estimate, −6.2 [95% CI, −11.8 to −0.1]). Conclusions: In CADASIL, WMHCC are likely related to secondary degeneration and are independently related to clinical severity, in contrast to the total burden of WMH.